Kinerja Bioreaktor Hibrid Anaerob dengan Media Batu untuk Pengolahan Air Buangan yang Mengandung Molase - Mindriany Syafila; Asis H. Djajadiningrat; Marisa Handajani (Journal of Mathematical and Fundamental Sciences, 2003)
Anaerobic hybrid bioreactor is a combination of suspended and attached growth systems. Stone was used as the microorganism attachment media. The feeding solution was made from molasses diluted to COD concentration of 10,000, 20,000, 30,000 and 40,000 mg/L. The hydraulic detention time was 30 hours and the height ratio between suspended and attached growth system was 0.5. The result shows that the organic concentration seems to be on of the determining factors. Furthermore, since the methane production was still low enough, it seems that the process has not achieved its optimum condition for methanogenic stage.